High temperature and ozone co-exposure induces cardiovascular damage in mice: Insights from gut microbiome and plasma metabolomics - Qiong Wu; Fei Xu; Yishu Yang; Aogang Zhang; Han Sun; Lin Yang; Shuaiqi Zhao; Yuling Zeng; Mengxin Wang; Saige Shi; Fengquan Zhang; Zhen An; et al. (Ecotoxicology and Environmental Safety)
Epidemiological studies have demonstrated associations between heat waves, ozone (O3) pollution, and cardiovascular morbidity and mortality. High temperature (HT) and higher levels of O3 usually co-exist in the atmosphere. However, few studies have investigated the adverse effects of HT and O3 co-exposure on cardiovascular system. Therefore, this study aimed to examine the effects of HT and O3 co-exposure on biomarkers of cardiovascular damage and potential mechanisms. Sixty-four healthy SPF male C57BL/6N mice, aged 8 weeks, were randomly allocated into four groups: control, O3, HT, and co-exposure (HT+O3). Mice inhaled filtered air or 1 ppm O3 at 24 °C or 36 °C, respectively, 4 h/day, for 5 consecutive days. Following the exposure, the biological samples of mice were collected for examination of biomarkers of cardiovascular disorders. Exposure to HT+O3 exacerbated cardiovascular pathological damage induced by HT or O3 alone. Compared to the control, the co-exposure group caused significant alterations of cardiovascular biomarkers. Moreover, co-exposure enhanced reduction of Lactobacillus and Ruminococcus and increases in Prevotella and Alistipe abundances induced by either HT or O3. Moreover, co-exposure also promoted O3-induced plasma metabolic disorder and these metabolites were enriched in multiple metabolic pathways typified by steroid hormone biosynthesis, biosynthesis of unsaturated fatty acids, and phenylalanine metabolism, among others. Spearman correlation analysis indicated that alterations of gut microbiota were significantly correlated with biomarkers of cardiovascular damage as well as plasma metabolic disorder. Exposure to HT and O3 leads to cardiovascular damage, which possibly implicates gut microbial dysbiosis and plasma metabolic disorder.